Deficiency in ZMPSTE24 and resulting farnesyl–prelamin A accumulation only modestly affect mouse adipose tissue stores[S] - Patrick J. Heizer; Ye Yang; Yiping Tu; Paul H. Kim; Natalie Y. Chen; Yan Hu; Yuko Yoshinaga; Pieter J. de Jong; Laurent Vergnes; Jazmin E. Morales; Robert L. Li; Nicholas Jackson; et al. (Journal of Lipid Research, 2020)
Zinc metallopeptidase STE24 (ZMPSTE24) is essential for the conversion of farnesyl–prelamin A to mature lamin A, a key component of the nuclear lamina. In the absence of ZMPSTE24, farnesyl–prelamin A accumulates in the nucleus and exerts toxicity, causing a variety of disease phenotypes. By ∼4 months of age, both male and female Zmpste24−/− mice manifest a near-complete loss of adipose tissue, but it has never been clear whether this phenotype is a direct consequence of farnesyl–prelamin A toxicity in adipocytes. To address this question, we generated a conditional knockout Zmpste24 allele and used it to create adipocyte-specific Zmpste24–knockout mice. To boost farnesyl–prelamin A levels, we bred in the “prelamin A–only” Lmna allele. Gene expression, immunoblotting, and immunohistochemistry experiments revealed that adipose tissue in these mice had decreased Zmpste24 expression along with strikingly increased accumulation of prelamin A. In male mice, Zmpste24 deficiency in adipocytes was accompanied by modest changes in adipose stores (an 11% decrease in body weight, a 23% decrease in body fat mass, and significantly smaller gonadal and inguinal white adipose depots). No changes in adipose stores were detected in female mice, likely because prelamin A expression in adipose tissue is lower in female mice. Zmpste24 deficiency in adipocytes did not alter the number of macrophages in adipose tissue, nor did it alter plasma levels of glucose, triglycerides, or fatty acids. We conclude that ZMPSTE24 deficiency in adipocytes, and the accompanying accumulation of farnesyl–prelamin A, reduces adipose tissue stores, but only modestly and only in male mice.